The Proteolytic Activation, Toxic Effects, and Midgut Histopathology of the Bacillus thuringiensis Cry1Ia Protoxin in Rhynchophorus ferrugineus (Coleoptera: Curculionidae) - Camilo Ayra-Pardo; Victor Ramaré; Ana Couto; Mariana Almeida; Ricardo Martins; José Américo Sousa; Maria João Santos (Toxins)
The red palm weevil (RPW; Coleoptera: Curculionidae) is a destructive pest affecting palms worldwide, capable of causing significant economic losses and ecological damage in managed palm ecosystems. Current management heavily relies on synthetic insecticides, but their overuse fosters resistance. Bacillus thuringiensis (Bt) offers a promising alternative, producing toxins selective against various insect orders, including Coleoptera. However, no specific Bt toxin has yet been identified for RPW. This study investigates the toxicity against RPW larvae of the Bt Cry1Ia protoxin, known for its dual activity against Lepidoptera and Coleoptera. A laboratory RPW colony was reared for two generations, ensuring a reliable insect source for bioassays. Cry1Ia was expressed as a 6xHis-tagged fusion protein in Escherichia coli and purified using nickel affinity. Incubation with RPW larval gut proteases for 24 h produced a stable core of ~65 kDa. Diet-incorporation bioassays revealed high Cry1Ia toxicity in neonate larvae. In contrast, the lepidopteran-active Cry1Ac protoxin, used as a robust negative control, was completely degraded after 24 h of in vitro proteolysis and showed no toxicity in bioassays. Cry1Ia-fed larvae exhibited significant midgut cell damage, characteristic of Bt intoxication. These findings highlight Cry1Ia’s strong potential for integration into RPW management programs.